Postoperative care of adult cardiac surgery patients. Issue 2 (February 2018) - El Diasty, Mohammad; Taberham, Rhona; Walcot, Nicholas
Abstract: Over 35, 000 cardiac operations are performed in the UK each year, with the majority requiring cardiopulmonary bypass (CPB). CPB replaces the heart and lung function temporarily by providing non-pulsatile oxygenated blood flow in order to facilitate arrested heart surgery. The use of an extracorporeal circuit and cardioplegia causes the release of pro-inflammatory cytokines inducing a systemic inflammatory response, coagulation cascade activation, haemodilution and transient myocardial depression among other effects. These manifest as a series of typical pathophysiological derangements, which require the adoption of a standard management strategy. The aim of this article is to provide an overview of the key issues including cardiac, respiratory, neurological, renal and haemostatic complications, which may arise while managing the postoperative cardiac surgical patient.